Contagion in futures metal markets during the recent global financial crisis: Evidence from Gold, Silver, Copper, Zinc and Aluminium - Konstantinos Tsiaras (SPOUDAI - Journal of Economics and Business, 2020)
This paper seeks to investigate the time-varying dynamic conditional correlations to the five most important future metal markets, namely Gold, Silver, Copper, Zinc and Aluminium. We employ a multivariate Fractionally Integrated Generalized ARCH (FIGARCH) dynamic conditional correlation (cDCC) model to generate the potential contagion effects between the markets. The under investigation period is during the period 2006-2011. Empirical results show the existence of contagion or the increase in dynamic conditional correlation for all the pairs of markets, indicating the correlations risky from an investor's point of view and implying the portfolio strategies difficult to apply. Additionally, Zinc is proved to be the most immune future metal market. The results are of interest to policymakers who provide regulations for the future metal markets.
Keywords: C58; C61; G11; G15; L61; 330; Financial contagion; Global Financial Crisis; cDCC-FIGARCH model; future metal market